2020
DOI: 10.1186/s12957-020-02040-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of lymph node parameters in distal cholangiocarcinoma after pancreaticoduodenectomy

Abstract: Background Pancreaticoduodenectomy is the only definitively curative therapy for the long-term survival of distal cholangiocarcinoma patients. Lymph node metastasis is widely accepted as an important prognostic factor for distal cholangiocarcinoma. The latest American Joint Committee on Cancer (AJCC) TNM classification system for distal cholangiocarcinoma has divided the lymph node metastasis patients into N1 and N2 by lymph node metastasis number. However, some studies suggested that the lymph node metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…The median OS time was 31 months and the 5-year survival rate was 18%. Lyu et al [ 19 ] reviewed the data of 123 patients with DCC after PD in a single center in China. The 5-year OS rate was 31.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The median OS time was 31 months and the 5-year survival rate was 18%. Lyu et al [ 19 ] reviewed the data of 123 patients with DCC after PD in a single center in China. The 5-year OS rate was 31.5%.…”
Section: Discussionmentioning
confidence: 99%
“…In the 7th edition of the AJCC TNM staging system, the N staging is mainly distinguished by the presence of regional lymph node metastasis. Several studies have confirmed that the number of regional PLNN can reflect the effect of lymph node metastasis on the prognosis of dCCA better when compared with the presence of lymph node metastases alone ( 26 30 ). The other two retrospective studies also found that patients with more than 11 lymph nodes removed had a better prognosis ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 95%
“…The LNR staging system combined with ELNN and PLNN compensates for the impact of insufficient ELNN on staging. A meta-analysis found that LNR = 0.2 is the ideal cutoff value for risk stratification of dCCA patients with radical resection ( 4 ), while the optimal cutoff value based on prognosis was between 0.45 and 0.17 ( 11 , 12 , 29 , 30 ). Similar cutoff values were obtained in our study by using X-tile software: LNR1-3: <0.1, 0.1 to 0.3, and ≥0.3.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Tsukahara et al, they demonstrated the survival rate of seven patients achieved R0 status after additional resection (sR0) was similar to that of pR0, and suggested additional resection was beneficial to some selected patients with positive margin of carcinoma in situ (CIS) (30). There were many series investigating prognostic factors of surgically treated dCCA patients, and the commonly identified factors were lymph node invasion, pancreatic invasion, perineural invasion, resection margin status, tumor grade, blood transfusion and adjuvant therapy (8,10,13,29,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 97%